WildLab: A naturalistic free viewing experiment reveals previously unknown electroencephalography signatures of face processing - Gert, Anna L.; Ehinger, Benedikt V.; Timm, Silja; Kietzmann, Tim C.; König, Peter (The European journal of neuroscience, 2022)
Neural mechanisms of face perception are predominantly studied in well‐controlled experimental settings that involve random stimulus sequences and fixed eye positions. Although powerful, the employed paradigms are far from what constitutes natural vision. Here, we demonstrate the feasibility of ecologically more valid experimental paradigms using natural viewing behaviour, by combining a free viewing paradigm on natural scenes, free of photographer bias, with advanced data processing techniques that correct for overlap effects and co‐varying non‐linear dependencies of multiple eye movement parameters. We validate this approach by replicating classic N170 effects in neural responses, triggered by fixation onsets (fixation event‐related potentials [fERPs]). Importantly, besides finding a strong correlation between both experiments, our more natural stimulus paradigm yielded smaller variability between subjects than the classic setup. Moving beyond classic temporal and spatial effect locations, our experiment furthermore revealed previously unknown signatures of face processing: This includes category‐specific modulation of the event‐related potential (ERP)'s amplitude even before fixation onset, as well as adaptation effects across subsequent fixations depending on their history. Here, we present findings from a combined eye‐tracking and EEG study on face processing. When free‐viewing natural scenes, we find similar ERPs to those in a passive perception task. Furthermore, effect sizes of both tasks correlate strongly (~.8), indicating a natural validity of prior results. Additionally, we find sequential effects of a fixation's history even before fixation onset. Taken together, our study facilitates classic ERP studies of face perception and shows that these brain signals are affected by past eye movements.